Women's needs in their journey towards motherhood via oocyte donation: A mixed methods systematic review - Hamideh Jafari; Ali Taghipour; Hosein Ebrahimipour; Robab Latifnejad Roudsari (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Given the significant changes in family formation through donation procedures, providing an optimal level of care that is responsive to the needs of mothers who get pregnant via oocyte donation is pivotal to improve their maternal role. Therefore, it is necessary to recognize the needs of oocyte donation mothers to address their specific needs. Objective: This study aimed to review the needs of women in their journey towards motherhood via oocyte donation. Materials and Methods: In this systematic review, which followed the updated Joanna Briggs Institute's methodological guidance for conducting a mixed methods systematic review, the quantitative observational and qualitative studies were searched through databases including PubMed, Web of Science, PsycINFO, the Cochran Library, and Google Scholar search engine. Letters to the editor, commentaries, magazine articles, articles without full text and abstracts presented in congresses were excluded. All English-language articles related to the needs of oocyte donation mothers, without time limitation, were reviewed. The eligible studies were critically appraised independently by 2 researchers. Results: 4649 records were identified from those 18 articles were finally included in the review. The needs of oocyte donation mothers comprised 8 categories: The need for special services in fertility clinics, the need to improve the quality of care, the need for emotional support and psychological consultation, information needs, the need for financial support, the need for disclosure counseling, educational needs, and the need for sociocultural and religious support. Conclusion: This review suggests various needs of oocyte donation mothers. The results can be used in carefully planning supportive programs for this vulnerable population.